Effect of fibre surface treatment on kenaf filled recycled polypropylene composite - Muhammad Remanul, Islam (2012)
Lignocelluloses based natural fibre is being used as an alternative to traditional glass and carbon fibre in the composite materials due to its low density and higher specific properties.Furthermore,these fibres are available at a very low cost.Current work is focused on kenaf fibre based reinforced recycled polypropylene composites.In this project,initially the raw kenaf fibre was grinded to a small size (2 to 5 mm) and then mixed with recycled polypropylene (RPP) followed by extrusion through a twinscrew extruder.Fibre loading in the composite was 10, 20, 30 40 and 50% by weight.After that test specimens for tensile, flexural and impact testing were prepared through an injection moulding machine.Melt flow indexer was used to evaluate theflow property of the extruded materials.To improve the interfacial property between fibreand matrix maleic anhydride grafted polypropylene (MAPP)was used as a coupling agent with ratio of 10:1.Mechanical tests showed that significant improvement achieved due to coupling agent.Fibre surface modifications for better adhesion between fibre and matrix were carried out by three ways including alkali,ultrasound and laccase enzyme treatment.Treated fibre was then blended with recycled polypropylene with 40%fibre loading in the presence of MAPP,as 40% loading found the optimum regarding tensile performances with untreated fibre based composites. For alkali treatment,both concentration of the solution and soaking time were considered as treatmentvariables for the fibre.Mechanical tests were carried out to evaluate the optimum treatment condition for the best strength.For ultrasound,normal water was used as media for the treatment.Both temperature and sonication power was considered as treatment variables.Mechanical tests were carried out to evaluate the best strength at optimum condition of fibre treatment.Enzymatic treatment was carried out for an alternative way of fibre treatment.The composites strength was increased by 18% for fibre loading whereas coupling agent improves it by 37%. Ultrasound and alkali treatment of fibre improved the tensile strength of the composites almost by 57%. Weathering and water uptake were carried out for the composites. After that mechanical tests were performed to evaluate the properties of the composites.Thermal test like thermogravimetric analysis (TGA) was carried out to evaluate the thermal stability of the composites.It was found that,RPP degrade at one stage while composites degrade at two stages.Activation energies of the composites were calculated from the TGA analysis.Crystallinity and melting point were detected through differential scanning calorimetry(DSC) analysis. Incorporation of fibre increased the crystallinity of the polymer matrix.Structural morphology was carried out of the fractured samples to evaluate the bonding interface between fibre and matrix.Improved adhesion between fibre and matrix was found for the case of treated fibre based composites in the presence of MAPP.Fourier transform of infrared radiation (FTIR)spectroscopy was used to find out any structural change due to the treatment of the fibre and analysis found that treatment of fibre able to remove the non-cellulosic compound to a varying extent depending on treatment parameters.Response surface method (RSM) was used to optimize process parameters and one of the best set of treatment conditions was 99.96% sonication power at 94.46oC to achieve 28.86 MPa of TS.